Association between temporal spatial parameters and overuse injury history in runners: A systematic review and meta-analysis - Brindle, R. A.; Taylor, J. B.; Rajek, C.; Weisbrod, A.; Ford, K. R. (Sports Medicine, 2020)
Background: Temporal spatial parameters during running are measurable outside of clinical and laboratory environments using wearable technology. Data from wearable technology may be useful for injury prevention, however the association of temporal spatial parameters with overuse injury in runners remains unclear. Objective: To identify the association between overuse injury and temporal spatial parameters during running. Data Sources: Electronic databases were searched using keywords related to temporal spatial parameters, running, and overuse injury, and authors` personal article collections through hand search. Eligibility Criteria for Selecting Studies: Articles included in this systematic review contained original data, and analytically compared at least one temporal spatial parameter (e.g. cadence) between uninjured and retrospectively or prospectively injured groups of runners. Articles were excluded from this review if they did not meet these criteria or measured temporal spatial parameters via survey. Study Appraisal and Synthesis Method: The internal validity of each article was assessed using the National Institutes of Health Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Meta-analyses were conducted for temporal spatial parameters if data existed from at least three separate cohorts of the same prospective or retrospective design. Data were pooled and analyzed using an inverse variance fixed-effect model. Results: Thirteen articles which tested a total of 24 temporal spatial parameters during running were included in the review. Meta-analyses were conducted on four temporal spatial parameters using data from eleven retrospective studies. Healthy runners and those with a history of overuse injury had a similar average stride time (mean difference: 0.00 s, 95% CI - 0.01 to 0.01 s), contact time (mean difference: 0.00 s, 95% CI 0.00 to 0.01 s), cadence (mean difference: 0.3 steps per minute (spm), 95% CI - 1.8 to 2.5 spm), and stride length (mean difference 0.00 m, 95% CI - 0.05 to 0.05 m) during running. Limitations: Data pooled for meta-analyses were limited to retrospective design studies. Studies included in the systematic review had low methodological consistency. Conclusion: Based on pooled results from multiple studies, stride time, contact time, cadence, and stride length averages are not distinguishable between runners either with or without a history of overuse injury. More prospective studies are required to determine the association of temporal spatial parameters with overuse injury development in runners.